(3TQM efXheI GHf CHj GdaQL GdeZQHi aj CfhGY GdMOjKs - (3GHf aQM , CMeO Hf aQM Hf CMeO Hf eMeO Hf aQM GddNej GdGTHjdj, TgGH GdOjf CHh GdYHGS,J (B966 (3g` s
(3ChdgG (B:s
(3bGd GdMGaX TgGH GdOjf Hf GdaQL GdeZQHi ZQGei UMjM hGdQLG ajc eYVd s
(3BNQgG (B:s
(3GdgeOGfi cdg HEScGf Gdeje hHGdOGd GdegedI s
(3GdfSNI HgG MhGTs
(3HBNQg PcQ ddVeGFQ bUjOI NeQi Uhai QGjb QHGfis
(3JSHjM ai XdGe Gddjds
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs